Synthesis, Characterization and Biological Activities of Cu(II), Co(II), Ni(II), Mn(II) and Fe(III) Complexes with Schiff Base Derived from 3-(4-Chlorophenoxymethyl)-4-amino-5-mercapto-1,2,4-triazole - Vidyavati Reddy; Nirdosh Patil; Tukaram Reddy; S. D. Angadi (E-Journal of Chemistry)
Coordination complexes of Cu(II),Co(II), Ni(II), Mn(II) and Fe(III)with Schiff bases derived from 3-(4-chlorophenoxymethyl)-4-amino-5-mercapto-1, 2, 4-triazole and substituted aldehydes have been synthesized. The complexes were characterized by elemental analysis, conductivity measurements, magnetic susceptibility data, electronic, IR, ESR and 1H NMR spectral data. On the basis spectroscopic studies, the Schiff base is monobasic bidentate ligand having the composition ML2(2H2O) Where M = Cu(II), Co(II), Ni(II) ,Mn(II), ML2(H2O)Cl Where M = Fe(III). Various physicochemical data suggest a six coordinated octahedral geometry for Cu(II),Co(II), Ni(II), Mn(II) and Fe(III) complexes. The antibacterial activities of ligand and its complexes were screened by cup plate method.